2007
DOI: 10.1089/ten.2006.0101
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Environmental Factors that Impact the Viability of Tissue-Engineered Constructs Fabricated by a Direct-Write Bioassembly Tool

Abstract: Tissue engineering combines the fields of medicine and engineering to build replacement tissue capable of restoring, maintaining, or improving damaged tissue. Researchers have recently developed techniques to fabricate tissue in which both the cells and matrix have a carefully defined architecture. This report details studies evaluating the use of a direct-write, 3-dimensional (3D) bioassembly tool (BAT) capable of extruding cells and matrix into spatially organized, 3D constructs. This system has been charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(49 citation statements)
references
References 19 publications
2
45
0
Order By: Relevance
“…Printed microvascular constructs were prepared using the BioAssembly Tool (BAT) 20 . The BAT is composed of a computer-controlled stage, that permits independent X and Y translation with 500 nm resolution, and a Z translational print head independently controlled with the same resolution.…”
Section: Methodsmentioning
confidence: 99%
“…Printed microvascular constructs were prepared using the BioAssembly Tool (BAT) 20 . The BAT is composed of a computer-controlled stage, that permits independent X and Y translation with 500 nm resolution, and a Z translational print head independently controlled with the same resolution.…”
Section: Methodsmentioning
confidence: 99%
“…[ 32 ] Others have reported that the applied pressure, nozzle diameter, cell type, and environmental conditions infl uence cell viability after printing. [ 33,34 ] Another important parameter is the total build time required to fabricate the desired engineered tissue construct. We anticipate that there is a maximum time over which these cell-laden inks can be stored in the ink reservoir prior to being harmed.…”
Section: Communicationmentioning
confidence: 99%
“…Two predominant approaches have arisen from the bioprinting technology, specifically those based on inkjet printing [100104] and mechanical extruders [105, 106]. Inkjet printing is a versatile, robust and a cost effective method, as it relies on direct printing of individual or pockets of cells.…”
Section: In Vitro Techniques For Vascularizationmentioning
confidence: 99%
“…Bioprinting can be utilized for generating small and intermediate diameter blood vessels using mechanical extruder-based techniques [105, 106]. In these approaches the exact purpose of the mechanical extruders is to place the ‘bio-ink’ or multicellular aggregated particles (that could be made of multiple cell types) with a defined composition into a supporting structure or ‘bio-paper’.…”
Section: In Vitro Techniques For Vascularizationmentioning
confidence: 99%